IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) GUNA MENINGKATKAN PEMAHAMAN MATERI NORMA PADA KELAS IV SEKOLAH DASAR - Awalia Putri Aisya; Triana Solikhah; Susilo Tri Widodo; Wulan Aulia Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to investigate the implementation of the Problem Based Learning (PBL) model in enhancing the understanding of normative material among elementary school students. The research subjects were 26 fourth-grade students at SD N 6 Kalipucang Wetan. Employing a qualitative descriptive approach, the study collected data through tests and non-tests. The analysis results indicate that PBL successfully increased students' understanding, with a 50% improvement from the pretest completion rate of 42.31% to 92.31% on the posttest. Additionally, there was a 23.07% increase in students' self-confidence and collaboration. This demonstrates that the implementation of the Problem Based Learning model effectively enhances the understanding of normative material for fourth-grade students. The research is expected to provide an innovative solution to address the lack of comprehension in normative material and contribute positively to the development of elementary school-level learning models.